Epileptology The Modern State of Science - Kalinin, Vladimir V. (IntechOpen, 2016)
Epilepsy seems to represent one of the most frequent neurological diseases and occurs in about 1% of the general population. Although epilepsy is known since antiquity, the precise data on its pathogenesis and effective treatment are still collected and nowadays represents an interest for neurologists and psychiatrists. Being a neurological disease, epilepsy is characterized by a broad palette of comorbid psychiatric disorders (affective and anxiety disorders, psychoses) that reduce the quality of life. Moreover, the risk of suicidal attempts in persons with epilepsy is much higher than in general population that once again increases the actuality of epilepsy research in many aspects. The book contains 13 chapters written by different authors from all over the world on different topics, including phenomenology, pathogenesis, and treatment in epilepsy. The modern data on these topics may be helpful for many specialists in the domain of epileptology.